Tabela de vida ecológica de bemisia tabaci (Genn.) Biótipo B (Hemiptera: Aleyrodidae) - de Albergaria, Nuno M. M. S. [UNESP]; Cividanes, Francisco J. [UNESP]; Dória, Háyda O.S. (My University, 2003)
This work was carried out aiming to obtain ecological life tables for Bemisia tabaci (Genn.) B-biotype in soybean. For that, successive artificial infestations were done in soybean plants, Glycine max (L.) Merril, FT 2000. Samples were made taking ten leaves randomly with intervals of three days, during eight generations of the whitefly. The number of living, dead and parasited insects and the age distribution were registered for each leaf. In this study the correlation coefficients for egg mortality (0,1954), 1st-instar nymphs (0,5610) and pupae (0,6168) were not significant, however 2nd- and 3rd-instar nymphs, showed significant coefficients 0,7978 and 0,8641 respectively, but the key factor was not identified. The parasitoid Encarsia spp. was the most important mortality factor in the pupae stage of B. tabaci B-biotype, but the correlation coefficient was not significant.
Ecological life table of bemisia tabaci (Genn.) B-biotype (Hemiptera: Aleyrodidae)
Keywords: Encarsia; Insecta; Population dynamics; Soybean; Whitefly